Bone-targeted mitochondrial delivery via magnetic-temperature responsive artificial cells for repairing age-related fractures - Nie, Shihao; Yu, Yue; Yan, Rong; Liu, Taoran; Du, Yue; Luo, Zhuojing; Li, Shengyou; Huang, Jinghui (Frontiers in Pharmacology, 2026)
BackgroundAge-related bone diseases, such as osteoporosis and degenerative joint disorders, pose a significant global health challenge, leading to over 9 million fractures annually, which not only diminishes quality of life but also imposes a substantial socioeconomic burden on healthcare systems. A major clinical obstacle in the aging population is the significantly reduced regenerative capacity of bone, often resulting in delayed fracture healing or nonunion fractures. Mitochondria, as the central regulators of cellular energy metabolism, are essential for determining cell fate and supporting tissue regeneration. However, age-associated mitochondrial dysfunction critically impairs these processes. While transplanting healthy mitochondria is a promising therapeutic strategy, its efficacy is severely limited by poor targeting efficiency and inherent fragility of mitochondria in circulation. Developing an efficient mitochondrial transplantation for elderly fractures is of great importance.MethodsWe constructed artificial cell microspheres (Fmito@ACs) containing mitochondria of fetal mouse mesenchymal stem cells and conducted systematic characterization of them. In vitro experiments evaluated the effects of Fmito@ACs on the functions of primary osteoblasts, and its role in delaying cellular senescence was analyzed through β-galactosidase staining and immunofluorescence analysis of senescence markers (P21 and γH2A.X). Its ability to restore mitochondrial function was assessed by measuring ROS, morphology, and energy metabolism. In animal experiments, labeled Fmito@ACs were tracked using IVIS Spectrum system, and their targeted accumulation at fracture sites guided by an external magnetic field was verified. The biosafety of the system was evaluated via H&E staining and hepatic/renal function parameters. Bone healing was monitored via micro-CT, X-ray, and histology on days 7, 14, and 21, while related gene expression and molecular mechanisms were analyzed by qPCR and transcriptome sequencing.ResultsFmito@ACs were successfully constructed and characterized, indicating a protective effect on mitochondria. The system ameliorated senescence in aged BMSCs, promoting osteogenesis by enhancing mitochondrial fusion and aerobic glycolysis. In an aged fracture model, Fmito@ACs showed targeted accumulation and biosafety, significantly improving healing.ConclusionAs an efficient mitochondrial-targeted delivery system, Fmito@ACs fully exploits the anti-aging effects of young mitochondria, providing a new strategy and theoretical basis for the treatment of age-related fractures.